2021
DOI: 10.3390/nu13020399
|View full text |Cite
|
Sign up to set email alerts
|

Sex May Modulate the Effects of Combined Polyphenol Extract and L-citrulline Supplementation on Ambulatory Blood Pressure in Adults with Prehypertension: A Randomized Controlled Trial

Abstract: Increased blood pressure (BP), vascular dysfunction and inflammation are involved in the etiology of cardiovascular disease (CVD). Although several dietary components such as polyphenols and L-citrulline may help to control BP, their combined impact on ambulatory BP in individuals at risk of CVD remains unknown. The objective of this research was to investigate the short-term impact of supplementation with a combination of polyphenol extract and L-citrulline on ambulatory BP, endothelial function and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Because Cit metabolism shows species differences, extrapolation of these findings to humans needs caution. Second, Cit metabolism is different between males and females; for example, the blood pressure‐lowering effects of Cit are more significant in women than men 102,103 ; these findings highlight the importance of considering sex differences on the impact of Cit when carbohydrate metabolism is evaluated. Third, most reported animal and human studies on the metabolic effects of Cit are from short‐term studies, with concerns remaining about their long‐term potential adverse effects 112 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Cit metabolism shows species differences, extrapolation of these findings to humans needs caution. Second, Cit metabolism is different between males and females; for example, the blood pressure‐lowering effects of Cit are more significant in women than men 102,103 ; these findings highlight the importance of considering sex differences on the impact of Cit when carbohydrate metabolism is evaluated. Third, most reported animal and human studies on the metabolic effects of Cit are from short‐term studies, with concerns remaining about their long‐term potential adverse effects 112 .…”
Section: Discussionmentioning
confidence: 99%
“…89 In addition, compared to men, women have lower Cit plasma flux, lower Arg/Cit, higher Cit/nitrite ratios in RBC and serum, 100 higher NOS-dependent NO production, 100 and higher wholebody NO biosynthesis. 101 Furthermore, the systolic and diastolic blood pressure-lowering effect of Cit is higher in women, 102,103 which is partially explained by the higher activity of the enzymatic machinery involved in Cit metabolism. In men, following administration of Cit (2-15 g), it is distributed in a volume of 15.2-17.2 L, and its plasma concentration rapidly (T max = 38-56 min) reaches a maximum level (C max = 515-3849 μM).…”
Section: L-citrulline Metabolismmentioning
confidence: 99%
“…Additionally, a cross-sectional analysis of a Korean population reported an inverse association between flavonoid intake and obesity in women, whilst for men a positive association was determined for some subclasses (namely, flavonols, flavanones and anthocyanidins) (101) . In a randomised double-blind parallel trial, a combination of 548 mg daily of polyphenols and 2 g daily of L-citrulline reduced ambulatory systolic blood pressure in women, but not in men (102) . Furthermore, a systematic review and meta-analysis described an inverse association between (poly)phenol consumption and gastric cancer.…”
Section: Plant Bioactivesmentioning
confidence: 99%
“…Table 2 shows the clinical trials related to grape polyphenols. In addition to cardiovascular disorders, a recently conducted variety of randomised controlled trials for metabolic syndrome related disorders including dementia, gut microbiota related research, periodontal diseases, allergic diseases, and cancer have revealed intriguing findings [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. These clinical trials have confirmed the benefits of the consumption of polyphenol phytochemicals for their risk-reducing effects in a variety of disorders.…”
Section: Grapesmentioning
confidence: 99%